Antibody Banding Patterns of the Enzyme-Linked Immunoelectrotransfer Blot and Brain Imaging Findings in Patients with Neurocysticercosis - Arroyo G. (2018)
This work was partially supported by the Fogarty International Center/NIH (training grant numbers D43TW001140 and D43TW007393) and by the National Council for Science, Technology and Innovation of Peru (CONCYTEC).